Analisis Semiotika dalam Video Animasi Berjudul “I am from Palestine” karya Rifk Ebeid - aisha nurdin; Aat Ruchiat Nugraha (Konvergensi, 2026)
The Palestinian issue has been widely discussed since October 2023, when the event known as Thufan Al Aqsa took place. Various media are used to share information, raise awareness, and advocate for justice regarding the genocide, including Instagram's "Add Yours" feature, hashtags, and animated videos. The short animated video titled "I Am from Palestine" is one of media examples that conveys messages and education about the Palestinian state. Furthermore, this video is a creative medium that advocates through compelling narratives and designs. This short animated video tells the story of a Palestinian girl studying in the United States and facing the reality of the normalization of the erasure of her homeland's identity in Western educational institutions. Using qualitative research methods, this study aims to analyze the meaning and construct visual symbols based on Roland Barthes's three levels of semiotic theory: denotation, connotation, and myth. The results of this study demonstrate the denotative and connotative meanings of Palestinian identity and existence, which then build myths related to the significant influence of educational institutions in shaping political beliefs or ideologies, the role of the family in preserving historical roots, and the continued existence of the Palestinian state. The results of this analysis prove that animated videos can play a role as an advocacy medium in building an ideology, in this context, the existence of a Palestinian state, and challenging the narrative of global hegemony amidst the current conflict